Effects of Muscarinic Receptor Antagonists With or Without M2 Antagonist Activity on Cholinergic Reflex Bronchoconstriction in Ovalbumin-Sensitized and -Challenged Mice - Hiroyasu Hirose; Jian Jiang; Masaru Nishikibe (Elsevier, 2003)
To investigate whether the inhibition of muscarinic M2 receptors results in the enhancement of reflex bronchoconstriction under airway hyperresponsiveness, we evaluated the effects of muscarinic antagonists with or without M2 antagonist activity on methacholine (MCh)- and SO2-induced airway responses in ovalbumin (OVA)-sensitized and -challenged mice. In this model, similar airway hyperresponsiveness to MCh (12 mg/ml) was observed on Days 31 and 37 (2.2-fold and 2.7-fold, respectively). However, airway hyperresponsiveness to SO2 (0.05 l/min) on Day 37 was less than that on Day 31 (4.0- and 2.7-fold on Days 31 and 37), indicating reflex bronchoconstriction was enhanced on Day 31 in comparison to Day 37. Ipratropium (0.03 - 0.3 mg/ml, inhalation) and Compound A (0.1 - 3 mg/kg, p.o.) inhibited MCh-induced responses on Days 31 and 37. Although ipratropium (0.03 - 1 mg/ml) dose-dependently inhibited SO2-induced responses on Day 31, ipratropium at a dose of 0.1 mg/ml significantly increased SO2-induced responses on Day 37 (162.2% of the corresponding control). On the other hand, Compound A (0.03 - 0.3 mg/kg, p.o.) inhibited SO2-induced responses without any increases on Days 31 and 37. These results suggest that two different conditions of reflex bronchoconstriction are presented in this model: 1) SO2-induced responses are enhanced by dysfunctional M2 receptors on Day 31; 2) the dysfunctional M2 receptors are partially restored on Day 37. In addition, the inhibition of the restored M2 receptors further enhance reflex bronchoconstriction.